Turning inward: Tocqueville and the structuring of reflexivity. Issue 5 (20th October 2017) - Williams, Lawrence H.
ABSTRACT: In this paper, I argue that the dominant view of reflexivity in contemporary social science is overly decontextualized, despite the value that reflexivity scholars have placed on the dynamic and active nature of individual thought and action. While this problem has been highlighted before, in terms of how habitual actions shape the way that individuals engage in reflexive thought, little attention has been given to the ways in which non-internalized elements of the environment condition this process. I illustrate my argument with examples from Tocqueville's classic text Democracy in America . I demonstrate how Tocqueville provided a framework for analyzing the way that societal-level norms and opportunity structures impact personal reflexive capacities. In this respect, his work is unparalleled and as such remains relevant to contemporary debates. I therefore argue for the application of Tocqueville's work into arenas it has seldom entered.